The Kajian Kualitas Air Tanah terhadap Keberadaan IPAL Komunal di Kecamatan Lumajang, Kabupaten Lumajang - Ainuddin, Nur Izzati Febriyan; Titah, Harmin Sulistiyaning (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2025)
The people of Lumajang District mostly use groundwater for sanitation hygiene purposes. The development of poorly planned residential areas has resulted in the existence of domestic wastewater management directly adjacent to the location of groundwater sources which causes the quality of groundwater not to comply with applicable quality standards. This study aims to determine the quality of groundwater from physical, chemical and microbiological parameters related to the existence of Communal IPAL in Lumajang District, Lumajang Regency. The determination of the groundwater sampling point was chosen at a location that had a distance of IPAL and was repeated twice. In this study, eight groundwater samples were taken with test parameters including pH, Fe, Mn, NO3, TDS, Color and total coliform which were then compared with Permenkes No. 2 of 2023 concerning Environmental Health. The results of the study showed that the quality of groundwater with a radius of IPAL did not meet the total coliform parameter in all samples, for the Fe parameter there were three samples that did not meet, for the Mn parameter two samples were found to not meet and for the TDS parameter two samples were found to not meet the applicable quality standards. The main factor causing the groundwater quality to be less than satisfactory is influenced by the technical aspect of communal wastewater treatment plant.